2014
DOI: 10.1111/aec.12155
|View full text |Cite
|
Sign up to set email alerts
|

Amphibian richness patterns inAtlanticForest areas invaded byAmerican bullfrogs

Abstract: The relationship between invasion success and native biodiversity is central to biological invasion research. New theoretical and analytical approaches have revealed that spatial scale, land‐use factors and community assemblages are important predictors of the relationship between community diversity and invasibility and the negative effects of invasive species on community diversity. In this study we assess if the abundance of Lithobates catesbeianus, the American bullfrog, negatively affects the richness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 59 publications
0
13
0
3
Order By: Relevance
“…Recent reviews confirm that invasive species use the breaches in the functional space as gateways to invade communities where they would not occur naturally or establish easily (Lososová et al, 2015;Finerty et al, 2016). For South American frogs this possibility is concrete, as several communities suffer from the invasion of the American bullfrog (Lithobates catesbeianus), including communities in the extreme south of Brazil (Both et al, 2014;Both & Melo, 2015). In terms of conservation, this is worrying, as the resilience of communities and the integrity of the ecosystem functions provided by native anurans may be compromised.…”
Section: Distance To Roads Influences the Patterns Of Functional Strumentioning
confidence: 99%
See 2 more Smart Citations
“…Recent reviews confirm that invasive species use the breaches in the functional space as gateways to invade communities where they would not occur naturally or establish easily (Lososová et al, 2015;Finerty et al, 2016). For South American frogs this possibility is concrete, as several communities suffer from the invasion of the American bullfrog (Lithobates catesbeianus), including communities in the extreme south of Brazil (Both et al, 2014;Both & Melo, 2015). In terms of conservation, this is worrying, as the resilience of communities and the integrity of the ecosystem functions provided by native anurans may be compromised.…”
Section: Distance To Roads Influences the Patterns Of Functional Strumentioning
confidence: 99%
“…In terms of conservation, this is worrying, as the resilience of communities and the integrity of the ecosystem functions provided by native anurans may be compromised. Indeed, the American bullfrog, for example, is among the world's 100 most prominent aquatic invasive species causing negative direct and indirect effect on native aquatic fauna worldwide, particularly on native anurans (Bucciarelli et al, 2014), and Brazil is no exception (Both et al, 2014;Both & Melo, 2015). Exotic plantations -of the genera Pinus and Eucalyptus -alter soil characteristics through the release of toxic substances, also contributing to lower quality litter (Machado, Moreira & Maltchik, 2012;Ferreira et al, 2015), making these areas inhospitable for anurans dependent on higher soil/water quality or the presence of vegetation for foraging or reproducing.…”
Section: Distance To Roads Influences the Patterns Of Functional Strumentioning
confidence: 99%
See 1 more Smart Citation
“…However, we do not exclude that they could have shown some signal if they had been analysed at a finer resolution. For instance, a study on bullfrog in Brazil showed that spatial heterogeneity had a significant effect when analysed at the aquatic-habitat scale, being positively correlated with bullfrog presence (Both et al, 2014).…”
Section: Diversity and Environmental Resistance Hypotheses Of Invasiomentioning
confidence: 99%
“…It has been suggested that bullfrogs might negatively affect various native species in Brazil, however there is a lack of evidence supporting such impacts (see Both et al 2014).…”
mentioning
confidence: 99%